IMPLEMENTATION OF PARFOR AND PARFOR EQUITY AT UFMA: CONTRIBUTIONS AND LIMITS TO THE DEMOCRATIZATION OF TEACHER EDUCATION - Moreira, Carlos José de Melo; Moreira, Verônica Lima Carneiro (Seven Editora, 2026)
Teacher education in basic education in Brazil has historically presented profound regional, social, and institutional inequalities, especially in states marked by educational vulnerabilities, such as Maranhão. In this context, public policies aimed at democratizing access to higher education become strategic for teacher appreciation and for improving the quality of basic education. The National Program for the Training of Basic Education Teachers (PARFOR) and, more recently, PARFOR Equity, were created to expand access to higher education for in-service teachers, prioritizing inland regions and historically marginalized groups. This study aimed to analyze the implementation processes of these programs at the Federal University of Maranhão (UFMA), highlighting their contributions and limitations regarding the democratization of teacher education. The research adopted a qualitative, descriptive, and exploratory approach, based on documentary analysis and bibliographic review. Institutional reports, legislation, public calls, and official documents from CAPES and UFMA were examined. The results indicate that the programs contributed to expanding access to teacher education courses, strengthening the interiorization of higher education, valuing cultural diversity, and reducing educational inequalities. Despite administrative, financial, and pedagogical challenges, PARFOR and PARFOR Equity demonstrate potential to consolidate equity policies and strengthen teacher education in Maranhão.